Methamphetamine-induced short-term increase and long-term decrease in spatial working memory affects protein Kinase M zeta (PKMζ), dopamine, and glutamate receptors - Braren, Stephen H.; Drapala, Damian; Tulloch, Ingrid K.; Serrano, Peter A. (Frontiers in Behavioral Neuroscience, 2014)
Methamphetamine (MA) is a toxic, addictive drug shown to modulate learning and memory, yet the neural mechanisms are not fully understood. We investigated the effects of 2 weekly injections of MA (30 mg/kg) on working memory using the radial 8-arm maze (RAM) across 5 weeks in adolescent-age mice. MA-treated mice show a significant improvement in working memory performance 1 week following the first MA injection compared to saline-injected controls. Following 5 weeks of MA abstinence mice were re-trained on a reference and working memory version of the RAM to assess cognitive flexibility. MA-treated mice show significantly more working memory errors without effects on reference memory performance. The hippocampus and dorsal striatum were assessed for expression of glutamate receptors subunits, GluA2 and GluN2B; dopamine markers, dopamine 1 receptor (D1), dopamine transporter (DAT) and tyrosine hydroxylase (TH); and memory markers, protein kinase M zeta (PKMζ) and protein kinase C zeta (PKCζ). Within the hippocampus, PKMζ and GluA2 are both significantly reduced after MA supporting the poor memory performance. Additionally, a significant increase in GluN2B and decrease in D1 identifies dysregulated synaptic function. In the striatum, MA treatment increased cytosolic DAT and TH levels associated with dopamine hyperfunction. MA treatment significantly reduced GluN2B while increasing both PKMζ and PKCζ within the striatum. We discuss the potential role of PKMζ/PKCζ in modulating dopamine and glutamate receptors after MA treatment. These results identify potential underlying mechanisms for working memory deficits induced by MA.